A Multi-Agent Extension of Hierarchical Task Network - Cardoso, Rafael C.; Bordini, Rafael H. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC); 2016: Anais do X Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações, 2016)
Describing planning domains using a common formalism promotes greater reuse of research, allowing a fairer comparison between different approaches. Common planning formalisms for single-agent planning are already well established (e.g., PDDL, STRIPS, and HTN), but currently there is a shortage of multi-agent planning formalisms with clear semantics. In this paper, we propose a multi-agent extension of the Hierarchical Task Network (HTN) planning formalism. Our formalism, the Multi-Agent Hierarchical Task Network (MA-HTN), can be used in the representation of multi-agent planning domains and problems. We provide a grammar for the domain and problem representation, and show a case study with the translation from a JaCaMo system, a multi-agent system development platform, to our MA-HTN formalism.